Quality of pomegranate peel by liquid fermentation with different microorganisms - ZHANG Man, ZHOU Menghan, SI Xinyu, YUE Hong, HU Yunfeng, GUO Honglian, HU Liwu (Zhongguo niangzao)
In order to deeply explore the value of pomegranate peel, a total of nine strains of yeasts, lactic acid bacteria and molds were selected for the liquid fermentation of pomegranate peels, respectively, and the contents of tannin, ellagic acid, total phenols, total flavonoids, total sugar and total fiber, antioxidant activity, color and volatile flavor substances in pomegranate peel were compared after 5 d of fermentation by different strains. The results showed that the contents of tannin (hydrolyzed tannin 0.16 mg/g, condensed tannin 6.23 mg/g) and total fiber (20%) were the lowest after fermentation by Aspergillus oryzae, the total sugar contents (3.5%) were the lowest after fermentation by Mucor sp., the contents of total flavonoids (6.45 mg/g) were the highest after fermentation by Monascus sp., and the contents of total phenols (98.54 mg/g) and ellagic acid (98.53 mg/g) were the highest after fermentation by Streptococcus thermophilus. After fermentation with Lactobacillus acidophilus, the scavenging rates of DPPH radical (90.98%), ABTS radical (85.03%), hydroxyl radical (36.60%) and superoxide anion radical (49.22%) were the highest, and the antioxidant capacity was the optimal. The color of pomegranate peel after fermentation by 5 strains of lactic acid bacteria was closer to that of fresh pomegranate peel, it was reddish brown after fermentation by Monascus sp., ginger after fermentation by A. oryzae and Mucor sp., and light yellow after fermentation by angel yeast. 4 strains of lactic acid bacteria and angel yeast had similar effects on the volatile components of pomegranate peel to a certain extent, and the components of pomegranate peel after fermentation by 3 strains of molds and Lactiplantibacillus plantarum were unique.